2009
DOI: 10.1371/journal.pone.0006963
|View full text |Cite
|
Sign up to set email alerts
|

Islet Endothelial Activation and Oxidative Stress Gene Expression Is Reduced by IL-1Ra Treatment in the Type 2 Diabetic GK Rat

Abstract: BackgroundInflammation followed by fibrosis is a component of islet dysfunction in both rodent and human type 2 diabetes. Because islet inflammation may originate from endothelial cells, we assessed the expression of selected genes involved in endothelial cell activation in islets from a spontaneous model of type 2 diabetes, the Goto-Kakizaki (GK) rat. We also examined islet endotheliuml/oxidative stress (OS)/inflammation-related gene expression, islet vascularization and fibrosis after treatment with the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 134 publications
(176 reference statements)
2
50
0
1
Order By: Relevance
“…Thus, previous studies using classical PSCs have demonstrated that hyperglycemia, 16,31 activation of the RAS, 32 oxidative stress, 17,30 platelet-derived growth factors, 33 and inflammatory cytokines 34 all enhance PSC activation and proliferation. The environment of the diabetic islet is characterized by the presence of the hyperglycemia [35][36][37] and oxidative stress, [38][39][40] as well as macrophage infiltration and increased expression of inflammatory molecules such as IL-1, IL-6, TNF-α, MCP-1, and MIP-1α.…”
Section: -1227mentioning
confidence: 99%
“…Thus, previous studies using classical PSCs have demonstrated that hyperglycemia, 16,31 activation of the RAS, 32 oxidative stress, 17,30 platelet-derived growth factors, 33 and inflammatory cytokines 34 all enhance PSC activation and proliferation. The environment of the diabetic islet is characterized by the presence of the hyperglycemia [35][36][37] and oxidative stress, [38][39][40] as well as macrophage infiltration and increased expression of inflammatory molecules such as IL-1, IL-6, TNF-α, MCP-1, and MIP-1α.…”
Section: -1227mentioning
confidence: 99%
“…GK rats were bred in our own colony at the University Paris-Diderot, together with Wistar control rats from the GK strain derived after backcrossing of animals selected at the upper limit of normal distribution for glucose tolerance [19]. Characteristics of GK rats have been previously described [1,[4][5][6]10,11,[18][19][20][21]. At the indicated age, rats were weighed, bled at time of decapitation and blood, liver and pancreas collected for analysis.…”
Section: Animalsmentioning
confidence: 99%
“…Serum leptin was measured using Luminex technology (Millipore, Zug, Switzerland) [5]. Plasma paroxonase-1 (PON-1) activity and lecithin: cholesterol acyltransferase (LCAT) activity were determined, as previously described [6,22].…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations